Pengaruh Strategi Pembelajaran dan Motivasi Belajar terhadap Pemahaman IPS Siswa Kelas V Sekolah Dasar - Ismaniati, Christina (MAJALAH ILMIAH PEMBELAJARAN, 2011)
The purposes of this study were to examine the effects of cooperative learning approach ofStudent Teams-Achievement Divisions (STAD), the level of student’s learning motivation, andthe interaction of the two independent variabels to understanding on social studies in elementarystudent. Cooperative learning was compared to lecture recitation cycle using a quasiexperimentaldesign. An achievement test consisting of items from the state competency test, anda motivation to learn questionnaire adopted from Hari Witono were administered. The analysisof variance(Anova) was used to data analyse. Anova showed a significant difference among thedependent variables from the learning strategies used. There was also a significant difference instudent’s understanding on social studies between the high and low levels of motivation to learn.But there was no interaction between the learning strategis and the levels of motivation to learntowards understanding on social studies in elementary school.Based on these findings,it wassuggested that teacher need to use cooperative learning type STAD and motivate students tolearn, so student’s achievement, especially in social studies subject matter, increased.